Effectiveness of “Isi Piringku” in Pregnant Women with Chronic Energy Deficiency - Endah Purwanti Handayani; Yustika Rahmawati Pratami; Siti Rohmawati (Indonesian Journal of Global Health Research, 2025)
This research is a 2024 KEMERDIKBUDRISTEK Grant research which is a development of one form of innovation in accordance with Health Technology Assessment which is able to answer the problems of pregnant women with chronic energy deficiency by providing measuring plates that can be a tool to help mothers every time they are going to eat. Objective to test the effectiveness of the "Isi Piringku" guidelines in improving the nutritional status of pregnant women with chronic energy deficiency. in this study is a Pre-Post Experimental Design with a one-group pretest posttest without control group design with a total sampling technique. The number of research respondents was 15 pregnant women who were studied for 1 month. The "Isi Piringku" media is effective in improving the nutritional status of pregnant women with chronic energy deficiency. The "Isi Piringku" media can be used for pregnant women with chronic energy deficiency in regulating meal portions to improve their nutritional status.